ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA TENAGA PENJUALAN - Asepta Hendriyanto (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
This study examines the performance of sales force management ofpublishers of IKAPI members (Ikatan Penerbit Indonesia) in Central Javaover the past two decades. antecedents to predict salesperson performanceand sales effectiveness as a consequence of salesperson's performance includethe company's strategic orientation, management control, sales area design,and salesperson performance. The results showed that all antecedents havea positive and significant effect on salesperson performance